2021
DOI: 10.3390/v13060953
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Viruses Pseudotyped with SARS-CoV-2 Spike Proteins Infect a Broad Spectrum of Human Cell Lines through Multiple Entry Mechanisms

Abstract: Severe acute respiratory syndrome-related coronavirus (SARS-CoV-2), the causative agent of coronavirus disease 19 (COVID-19), enters cells through attachment to the human angiotensin converting enzyme 2 (hACE2) via the receptor-binding domain (RBD) in the surface/spike (S) protein. Several pseudotyped viruses expressing SARS-CoV-2 S proteins are available, but many of these can only infect hACE2-overexpressing cell lines. Here, we report the use of a simple, two-plasmid, pseudotyped virus system comprising a S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 41 publications
0
29
0
Order By: Relevance
“…Finally, we examined whether the SARS-CoV-2 inhibitory effect of defensins was cell-type-dependent. Intestinal epithelial cells (Caco-2) express moderate levels of endogenous hACE2, and lung epithelial cells (A549) have near undetectable levels of hACE2 but a high abundance of SARS-CoV-2 alternative receptors, CD147 and tyrosine-protein kinase receptor UFO (AXL) [ 28 ]. We found that HNP1, HD5 and RC101 exhibited anti-SARS-CoV-2 activity in both Caco-2 and A549 cells ( Figure 8 B), indicating that the inhibitory effect of defensins on viral infection was not receptor-specific or cell-type-dependent.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, we examined whether the SARS-CoV-2 inhibitory effect of defensins was cell-type-dependent. Intestinal epithelial cells (Caco-2) express moderate levels of endogenous hACE2, and lung epithelial cells (A549) have near undetectable levels of hACE2 but a high abundance of SARS-CoV-2 alternative receptors, CD147 and tyrosine-protein kinase receptor UFO (AXL) [ 28 ]. We found that HNP1, HD5 and RC101 exhibited anti-SARS-CoV-2 activity in both Caco-2 and A549 cells ( Figure 8 B), indicating that the inhibitory effect of defensins on viral infection was not receptor-specific or cell-type-dependent.…”
Section: Resultsmentioning
confidence: 99%
“…Since RC101 is known to inhibit Japanese encephalitis virus protease [ 51 ], investigations into the effects of defensins on serine protease are warranted. Additionally, alternative receptors including CD147 and AXL for SARS-CoV-2 viral entry have been reported, particularly in cells with a low abundance of hACE2 [ 28 , 52 , 53 ]. We have shown that pseudotyped viruses expressing SARS-CoV-2 spike proteins enter A549 cells through CD147 in a spike RBD-independent manner [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 18 Other laboratory also reported the involvement of CD147 in SARS-CoV-2 viral entry. 19 However, whether CD147 can mediate cellular entry of SARS-CoV-2 variants remains unclear. In addition, whether CD147, as a signaling transducer, plays a role in the inflammation of COVID-19 diseases and contributes to cytokine storm in severe cases is unknown.…”
Section: Introductionmentioning
confidence: 99%